Designing and fabrication of phenothiazine and carbazole based sensitizers for photocatalytic water splitting application. (6th September 2018) - Kumar, Nadavala Siva; Dhar, Abhishek; Ibrahim, Ahmed A.; Vekariya, Rohit L.; Bhadja, Poonam
Abstract: In the present work, we have designed and synthesized two carbazole and phenothiazine donor moieties based metal-free organic sensitizers and their codes are WCBZ2 and WPTZ2 respectively. These sensitizers have been used for photocatalytic hydrogen (H2 ) evaluation application. The sensitizers exhibit good light absorption capability and electrochemical properties as well. For increasing water splitting capacity, incorporate platinum salt on TiO2 semiconductor photoanode was performed and compared hydrogen evolution with pure TiO2 photoanode. We have also studied the influence of the sensitizer's concentration and the effect of pH of the medium was explored. Using a theoretical measurement optimized both the synthesized dimer dyes structure geometry and the calculated their HOMO-LUMO energy level. Here also reported optimized pH and concentration of sensitizers in the reaction medium and found that the high hydrogen generation efficiency from water splitting is 138.3 μmol (348 TONs) by the WPTZ2 dye. Graphical abstract: Image 1 Highlights: Carbazole and phenothiazine donor moieties based metal free organic sensitizers have been designed and synthesized. Sensitizers have been used for photocatalytic hydrogen (H2 ) evaluation application. The sensitizers exhibit good light absorption capability and electrochemical properties. High hydrogen generation efficiency from water splitting is 138.3 μmol (348 TONs) by WPTZ2 dye.